Analisis Kesulitan Menyelesaikan Soal Persamaan Garis Lurus Ditinjau dari Kecemasan Belajar Matematika - Muhammad Darwis M; Asdar; Irda Al Adawiyah (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2022)
This study aims to determine the students' difficulties in solving straight-line equations in terms of anxiety in learning mathematics in class VIII SMP. The method of this research is descriptive qualitative research. There are three students who are the subject of this study, namely one student with high anxiety, one student with moderate anxiety, and one student with low anxiety. The results showed that subjects with high anxiety (SKT) had more difficulty in solving questions and needed a relatively long time to solve problems. Subjects of moderate anxiety (SKS) had little difficulty in applying concepts and more difficulties in applying principles and difficulties in solving verbal problems and took a long time to solve problems. The subject of low anxiety (SKR), has no difficulty in understanding concepts, applying principles, and has no difficulty in solving verbal problems but requires a relatively long time in solving questions. The results of this study are expected to add insight and minimize students' difficulties in solving straight line equations